Effect of Sun Dried, Dehulled and Boiled Kidney beans on Hematological and Serum Biochemistry of Broiler Chickens - Okonkwo, J. C.; Umegwuagu, J. I.; Okonkwo, I. F.; Onunkwo, D. N. (International Journal of Environment, Agriculture and Biotechnology, 2019)
A four-week feeding trial was conducted to assess the effect of sun dried (raw) (SD), dehulled (D) and boiled kidney beans (BKB)on the haematological and serum biochemistry of broiler birds. One hundred and twenty unsexed broiler birds were used for the study. The birds were randomly assigned to four dietary treatments replicated three (3) times with twelve (12) birds per replicate in a completely randomized design (CRD). The treatment groups were control diet (CD), sun dried kidney bean (SDKB), dehulled kidney bean (DKB) and boiled kidney bean (BKB), designated as T1, T2, T3 and T4, respectively. The feeding trial lasted for four weeks.The proximate composition of the kidney beans used was also determined. The proximate composition obtained showed that kidney beans is a good protein source for birds (crude protein content of 20.98%). At the end of the feeding trial, blood samples were collected and the haematological and serum biochemical parameters of the birds were determined using standard methods. Generally, the diets used exhibited significant effects on both the haematological and serum biochemical parameters of the birds studied. Diet without kidney bean (Control) and diet containing sun dried kidney bean gave the best result, though all the haematological and biochemical values obtained in the studyfall within the referral range indicating that processing method had no negative effect on the haematological and serum biochemical parameters of the birds. Based on the findings in this study, it was recommended that kidney bean is a good source of plant protein in animal diet and does not necessarily need to be processed prior to its incorporation in animal feed.